تقويم القواعد العربية بمظاهرة كتاب التراث بمركز اللغة العربية بمعهد مفتاح العلوم بانيبين بالنجائن باميكاسان - Taufiqurahman (Tanfidziya: Journal of Arabic Education, 2022)
Evaluation is an important component in the learning process and system. As in the initial observation, the Miftahul Ulum Panyeppen Islamic Boarding School in Pamekasan carried out an evaluation in measuring the qawaid ability of students using a unique evaluation form that was rarely encountered before, namely using the Fathul Qorib book as evaluation material. This study has two focuses, namely knowing the application and the advantages and disadvantages of implementing the Qawaid Arabiyah evaluation using the Fathul Qorib Book at the Miftahul Ulum Panyeppen Islamic Boarding School in Pamekasan.                The research method used in this study is a qualitative method with three data collection techniques, namely interviews, observation and documentation               The results of this study indicate that: First, the implementation of the Qawaid Arabiyah Evaluation using the Fathul Qorib Book at the Miftahul Ulum Panyeppen Islamic Boarding School in Pamekasan through several steps as follows (1) sorting students based on ability levels. (2) say hello and ask students to open, choose a title and read. (3) Demonstrating the contents of the text in the book by explaining the grammatical position in the reading, (4) the teacher asks the students to determine the main ideas in the reading text. (5) Cover.               While the advantages and disadvantages of implementing the Qawaid Arabiyah Evaluation using the Fathul Qorib Book at the Miftahul Ulum Panyeppen Islamic Boarding School in Pamekasan have been found, namely that the number of advantages contained in the evaluation process is more than the disadvantages.